2020
DOI: 10.3389/feduc.2020.583881
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenon of Moving to Online/Distance Delivery as a Result of COVID-19: Exploring Initial Perceptions of Higher Education Faculty at a Rural Midwestern University

Abstract: The purpose of this study was to explore the initial perceptions and experiences of faculty whose classes were moved to an online/distance delivery as a result of the COVID-19 pandemic. Using mixed methods online survey methodology, the researchers sought to describe faculty perceptions relative to their response to moving all university courses online within the timeframe allotted by university leadership. Building upon this groups' previous research, which focused on the relationships among care and rigor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 39 publications
0
37
0
4
Order By: Relevance
“…Recently published research from Germany, Australasia, India and the United States has explored educator experiences of emergency remote teaching during the COVID-19 pandemic (Cameron-Standerford et al, 2020;Gamage et al, 2020;Irtifa and Richa, 2020;König et al, 2020;Marshall et al, 2020;Pather et al, 2020). However, to date, there is limited research on the experiences of academics during the pandemic, including support mechanisms and unintended benefits.…”
Section: Teaching and Learning Remotely In An Emergencymentioning
confidence: 99%
“…Recently published research from Germany, Australasia, India and the United States has explored educator experiences of emergency remote teaching during the COVID-19 pandemic (Cameron-Standerford et al, 2020;Gamage et al, 2020;Irtifa and Richa, 2020;König et al, 2020;Marshall et al, 2020;Pather et al, 2020). However, to date, there is limited research on the experiences of academics during the pandemic, including support mechanisms and unintended benefits.…”
Section: Teaching and Learning Remotely In An Emergencymentioning
confidence: 99%
“…Even though there is little information available on the perception of students concerning emergency remote teaching, still preliminary research has suggested a rather negative perception towards this mode of studying, while also showing gratitude and understanding for the exceptional circumstances [16,18]. In a related study, preliminary perceptions in higher education were analysed, and Cameron-Standerford et al [20] noted that "challenging", "concern", and "anxious" were…”
Section: Related Work About Emergency Remote Teachingmentioning
confidence: 99%
“…Nevertheless, it is encouraging to see other teacher educators have begun to reflect on the implications to pedagogy and practice. These included a number of Frontiers articles (Siemens, 2005;Burns et al, 2020;Cameron-Standerford et al, 2020;Jones and Kessler, 2020;Thomas, 2020;Allo, 2020) as well as other peer reviewed articles (Johnson et al, 2020;McCormack, 2020;Prince et al, 2020;Rapanta et al, 2020). In addition, there has been a plethora of non-peer reviewed publications included in educational websites to support practitioners, administrators, and students as they seek success in alternate delivery modes of teaching and learning in higher education (Academic Matters, Canadian Digital Learning Research Association, CAUT, Educause, Every Learner Everywhere, Inside Higher Education, Online Learning Consortium, The Chronicle, TEACHONLINE).…”
Section: Literature Reviewmentioning
confidence: 99%
“…All of the studies reviewed in the recent literature cite a need for presence in the alternate delivery mode (Cameron-Standerford et al, 2020;Coman et al, 2020;Jones & Kessler, 2020;Murdock and Williams, 2020;Prince et al, 2020;Rapanta et al, 2020;Thomas, 2020). Strategies are cited in some of the peer reviewed literature to support the pivot.…”
Section: Teaching Strategies For Alternate Delivery Modelsmentioning
confidence: 99%
See 1 more Smart Citation